Attitudes towards risk-stratified breast cancer screening among women in England: A cross-sectional survey. (September 2020) - Ghanouni, Alex; Sanderson, Saskia C; Pashayan, Nora; Renzi, Cristina; von Wagner, Christian; Waller, Jo
Objectives: Risk stratification may improve the benefit/harm ratio of breast screening. Research on acceptability among potential invitees is necessary to guide implementation. We assessed women's attitudes towards and willingness to undergo risk assessment and stratified screening. Methods: Women in England aged 40–70 received summary information about the topic, and completed face-to-face computer-assisted interviews. Questions assessed willingness to undergo multifactorial breast cancer risk assessment, more frequent breast screening (if at very high risk), or less frequent or no screening (if at very low risk), and preferences for delivery of assessment results. Results: Among 933 women, 85% considered breast cancer risk assessment a good idea, and 74% were willing to have it. Among 125 women unwilling to have risk assessment, reasons commonly related to 'worry' (14%) and 'preferring not to know' (14%). Among those willing to have risk assessment ( n = 689), letters/emails were generally preferred (42%) for results about very low-risk status. Face-to-face communication was most commonly preferred for results of very high-risk status (78%). General practitioners were most commonly preferred sources of assessment results (≈40%). Breast cancer specialists were often preferred for results of very high-risk status (38%). Risk-stratified breast screening was considered a good idea by 70% and 89% were willing to have more frequent screening. Fewer would accept less (51%) or no screening (37%) if at very low risk. Conclusions: Women were generally in favour of multifactorial breast cancer risk assessment and risk-stratified screening. Some were unwilling to accept less or no screening if at very low risk.